Virtual-learning content management system : design and implementation using Joomla for eLearning and problem-based learning courses - ashikin, Norul; Gunawan, Teddy Surya; Kartiwi, Mira (LAP LAMBERT Academic Publishing GmbH & Co. KG, 2012)
Nowadays, the popular methods of information delivering include e-learning, cyber-learning, and other terms that describe the new ways of learning. In order to improve the learning process, the Virtual Learning Content Management System (V-LCMS) for Problem-Based Learning (PBL) Courses developed at the College of Professional MARA Indera Mahkota. The proposed system aims to develop a website using iterative and incremental development prototype. The programming language chosen is PHP 5.2.5, MySQL 5.0 as the database and Apache 2.2.8 as the web server. The V-LCMS enables easier teaching and learning process between instructors and students.